Understanding how Malay language student teachers perceive their subject matter knowledge - Abd Rahman, Fadzilah; Jusoh, Zuraini (Universiti Putra Malaysia Press, 2012)
Teachers’ subject matter knowledge is believed to be an essential attribute for effective teaching and promoting successful student learning. It is important for teachers to know deeply about the subject they are teaching and how to link the knowledge to other disciplines. Ambiguity remains, however, warranting further research as to how student teachers’ view subject matter knowledge. This study aimed to look into student teachers’ subject matter knowledge as they are still in the stage of learning to teach. Semi-structured interviews with ten Malay language student teachers were carried out. Six themes emerged from the analysis: subject contents, fluent grammar, current issues, depth of knowledge, method of teaching and importance of the subject taught. The results of this study may help in increasing teachers’ awareness of the importance of having deep subject knowledge or in-depth of the subject in their own disciplines of teaching. These would also help in designing an effective teacher education programme that emphasizes on the development of student teachers’ subject matter knowledge.